LINC01232 regulates miR-516a-5p/BCL9 axis to promote triple-negative breast cancer progression: LINC01232 and TNBC progression - liu, wei; Niu, Yunfeng; An, Jie (Cellular and Molecular Biology, 2025)
Triple-negative breast cancer (TNBC) is characterised by an absence of the oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), for which there are few therapeutic options and the prognosis is poor. This research sought to explore the particular function of the long non-coding RNA (lncRNA) LINC01232 in TNBC and its regulatory impacts on the miR-516a-5p/BCL9 pathway. In this study, quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to determine the expression level of LINC01232 in TNBC tissues. We also examined its regulatory influences on miR-516a-5p and BCL9 via cellular function tests and a luciferase reporter experiment. Evaluated the effect of LINC01232 silencing on proliferation, migration and invasion of breast cancer cells. Results showed that LINC01232 expression was abnormally high in TNBC tissues in comparison to normal tissues. Inhibition of LINC01232 expression markedly impeded breast cancer cell proliferation, clone formation, migration and invasion. We found that LINC01232 competes with miR-516a-5p for binding, thereby reducing its expression and subsequently increasing BCL9 expression. In conclusion, our results indicate that LINC01232 facilitates the malignant development of TNBC through the miR-516a-5p/BCL9 pathway, providing fresh perspectives on the pathogenesis of TNBC and pinpointing potential therapeutic targets.